Deepening Neoliberalism via Austerity and 'Reform': The Case of Ireland. Issue 2 (July 2013) - Fraser, Alistair; Murphy, Enda; Kelly, Sinéad
The current economic crisis – the 'great recession' – raises numerous questions about neoliberal ideas and practice, not the least of which is whether (and if so, how) neoliberalism can survive it. Our paper takes on these issues using the case of Ireland. This is the first proper neoliberal crisis in Ireland. From the early 1990s to 2008, Ireland was held up by many neoliberal champions as a place that gained from deregulation, openness to inward investment, and low corporation tax rates. But the build-up of contradictions in Ireland exploded rapidly in 2008, when its property bubble burst and private banks and government finances collapsed. Rather than examining what caused Ireland's crisis, we look at what has happened between 2008 and 2013. We focus on structural adjustments regarding the property, finance, and labour markets and then on the government's austerity programme as a whole. In addition to demonstrating how these adjustments have been an attack on workers and ordinary citizens, we identify some particularly striking elements, which we use to argue that a new phase of disturbance and restructuring is deepening and extending neoliberalism's influence in Ireland.